2020
DOI: 10.1038/s42004-020-0281-6
|View full text |Cite
|
Sign up to set email alerts
|

Formation of thioglucoside single crystals by coherent molecular vibrational excitation using a 10-fs laser pulse

Abstract: Compound crystallization is typically achieved from supersaturated solutions over time, through melting, or via sublimation. Here a new method to generate a single crystal of thioglucoside using a sub-10-fs pulse laser is presented. By focusing the laser pulse on a solution in a glass cell, a single crystal is deposited at the edge of the ceiling of the glass cell. This finding contrasts other non-photochemical laser-induced nucleation studies, which report that the nucleation sites are in the solution or at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Since then, a considerable number of studies have been reported with various types of chemical compounds and by employing an array of laser systems whose properties/parameters including time duration (continuous, femtosecond, picosecond, nanosecond regime), field polarization (linear, circular and elliptical), wavelength (UV–vis–IR), or intensity (ionizing, nonionizing), were altered to control primary nucleation. However, despite the remarkable scientific progress, the underlying mechanism behind the laser-induced nucleation still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a considerable number of studies have been reported with various types of chemical compounds and by employing an array of laser systems whose properties/parameters including time duration (continuous, femtosecond, picosecond, nanosecond regime), field polarization (linear, circular and elliptical), wavelength (UV–vis–IR), or intensity (ionizing, nonionizing), were altered to control primary nucleation. However, despite the remarkable scientific progress, the underlying mechanism behind the laser-induced nucleation still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed laser-induced crystallization of organic molecules has been known since 1996 by Garetz et al and has been advanced in the early 2000s by Okutsu et al , and Yoshikawa et al , Mainly small molecules, amino acids, and small proteins have been crystallized with pulsed lasers so far.…”
Section: Introductionmentioning
confidence: 99%